2017
DOI: 10.1038/srep42175
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Variant in IL-37 Confers A Significant Risk of Coronary Artery Disease

Abstract: The interleukin 1 family plays an important role in the immune and inflammatory responses. Coronary artery disease (CAD) is a chronic inflammatory disease. However, the genetic association between IL-37, the seventh member of the IL-1 family, and CAD is unknown. Here we show that a single nucleotide polymorphism in the IL-37 gene (rs3811047) confers a significant risk of CAD. We have performed an association analysis between rs3811047 and CAD in two independent populations with 2,501 patients and 3,116 control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
(62 reference statements)
0
26
1
Order By: Relevance
“…Previous studies have shown that common genetic variation in IL37 has clinically relevant effects in inflammatory diseases. For example, rs3811047 is associated with the development of coronary artery disease and susceptibility to Mycobacterium tuberculosis infection 38 39. Additionally, rs2723187 has been associated with rapid degradation and significantly lower levels of IL-37 protein, with consequently reduced anti-inflammatory properties 40.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that common genetic variation in IL37 has clinically relevant effects in inflammatory diseases. For example, rs3811047 is associated with the development of coronary artery disease and susceptibility to Mycobacterium tuberculosis infection 38 39. Additionally, rs2723187 has been associated with rapid degradation and significantly lower levels of IL-37 protein, with consequently reduced anti-inflammatory properties 40.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have investigated the potential role of natural variants of the IL‐37 gene in human disease, including M. tuberculosis infection (Liu et al, ), coronary artery disease (Yin et al, ), and rheumatoid arthritis (Pei et al, ). In general, variants linked to increased production of IL‐37 and/or greater IL‐37 signaling are associated with lower disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the single nucleotide polymorphism (SNP) rs3811047 (threonine‐alanine change in amino acid 42 of exon 2) is associated with reduced disease severity in patients with rheumatoid arthritis . A different study in Chinese patients found that SNPs in the IL‐37 gene associated with decreased levels of expression confers a significant risk of coronary artery disease . In genetic carriers of IL‐37 haplotype2, most common among individuals of African descent, reduced levels of IL‐37 may predispose to the development of stronger inflammatory responses …”
Section: Role Of Il‐37 In Inflammatory Human Diseasementioning
confidence: 99%